Iron-based catalyst, preparation method and application thereof, and FTO reaction
By using iron-based catalysts of elements such as Fe, Mn, Nb, Cs and La in the FTO reaction, prepared by precipitation and calcination, and performing reduction and carbonization treatment, the carbon monoxide conversion rate and the conversion of existing iron-based catalysts in the FTO reaction are solved. The problem of low selectivity of low carbon olefins has achieved efficient CO conversion and low carbon deposit characteristics.
Patent Information
- Application Number
- CN202310874887.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-07-17
AI Technical Summary
The existing iron-based catalysts have low carbon monoxide conversion and low-carbon olefin selectivity in the FTO reaction, and are insufficient in the resistance to carbon deposits.
An iron-based catalyst containing elements such as Fe, Mn, Nb, Cs and La was prepared by precipitation reaction and calcination, combined with reduction and carbonization treatment, and was used in the FTO reaction to improve catalytic activity and selectivity.
High CO raw material conversion rate and C2-C4 olefin selectivity are achieved, and the carbon deposit amount is maintained during long-term use, which significantly improves the resistance to carbon deposit of the catalyst.
Smart Images

Figure BDA0004342568990000151 
Figure BDA0004342568990000161
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to an iron-based catalyst, a preparation method and application thereof, and a FTO reaction. Background Art
[0002] Iron-based catalysts are commonly used for direct production of low-carbon olefins. The preparation process, additives and treatment methods have a great influence on the catalyst activity and selectivity. Alkaline metal additives have attracted attention as an important electronic additive for Fe-based catalysts. Alkali metal elements have a significant promoting effect on Fe-based catalysts for Fischer-Tropsch synthesis, and the promotion efficiency is roughly proportional to the alkalinity. Mn additives also have a certain electron donating effect, which can change the binding energy of species on the sample surface. Some studies have shown that MnO can promote the dissociative adsorption of CO and weaken the adsorption of H2, so it will inhibit the hydrogenation process on the catalyst surface to a certain extent, thereby improving the selectivity of olefins in the product.
[0003] CN105854915A discloses a catalyst for preparing light olefins from synthesis gas and a preparation method thereof. The catalyst comprises Mg, Fe, M and K, wherein M is Zn, Al or Mn, and is prepared by coprecipitation, normal pressure crystallization and finally impregnation with a K source. The catalyst is used for directly preparing light olefins from CO hydrogenation, wherein the CO single-pass conversion rate is greater than 70%, the olefin ratio (O / P) is greater than 5.0, and the weight distribution of C5+ total hydrocarbons is less than 15wt%. The preparation process of the catalyst is simple and has good repeatability, but the carbon monoxide conversion rate and light olefin selectivity are both low. Summary of the invention
[0004] The purpose of the present invention is to provide a new iron-based catalyst and a preparation method thereof. When the iron-based catalyst is used in a FTO reaction, the catalyst has excellent catalytic activity, so that both the carbon monoxide conversion rate and the light olefin selectivity are high.
[0005] In order to achieve the above object, the first aspect of the present invention provides an iron-based catalyst, which includes a carrier and an active component. In terms of atomic ratio, the chemical formula of the active component expressed as an oxide is as follows:
[0006] Fe 100 Mn a Nb b Cs c A d B e O x ,
[0007] A is selected from non-ferrous metal elements of Group VIII and / or elements of Group VIB;
[0008] B is selected from La series elements;
[0009] The value range of a is 30.0-130.0;
[0010] The value range of b is 1.0-20.0;
[0011] The value range of c is 0.1-10.0;
[0012] The value range of d is 1.0-60.0;
[0013] The value range of e is 0.1-10.0;
[0014] x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst.
[0015] The second aspect of the present invention provides a method for preparing the iron-based catalyst of the present invention, the preparation method comprising:
[0016] (1) In the presence of a precipitant, a solution containing an Fe source, a Mn source, a Nb source and an A source undergoes a precipitation reaction;
[0017] (2) The precipitate obtained by the precipitation reaction in step (1) is mixed with the carrier source, Cs source solution, pH adjuster, and B source solution in sequence, and then dried and calcined.
[0018] The third aspect of the present invention provides the use of the iron-based catalyst of the present invention in a FTO reaction.
[0019] A fourth aspect of the present invention provides a FTO reaction, in which H2 and CO are contact-reacted in the presence of the iron-based catalyst of the present invention.
[0020] Through the above technical scheme, the new iron-based catalyst provided in the present invention has excellent resistance to carbon deposition when used, and can obtain high CO feedstock conversion rate and C2-C4 olefin selectivity when used in FTO reaction. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] The first aspect of the present invention provides an iron-based catalyst, which includes a carrier and an active component. The active component is represented by an oxide and has a general chemical formula as follows, calculated by atomic ratio:
[0023] Fe 100 Mn a Nb b Csc A d B e O x ,
[0024] A is selected from non-ferrous metal elements of Group VIII and / or elements of Group VIB;
[0025] B is selected from La series elements;
[0026] The value range of a is 30.0-130.0;
[0027] The value range of b is 1.0-20.0;
[0028] The value range of c is 0.1-10.0;
[0029] The value range of d is 1.0-60.0;
[0030] The value range of e is 0.1-10.0;
[0031] x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst.
[0032] The active components of the iron-based catalyst in the present invention contain Fe, Mn, Nb, Cs, A and B elements. The active components are expressed as oxides, which does not mean that Fe, Mn, Nb, Cs, A and B elements are all present in the iron-based catalyst in the form of oxides. Among them, Fe, Mn, Nb, Cs, A and B elements exist in at least one form of atoms, oxides and carbides. The chemical formula in which the active components are expressed as oxides in the present invention only refers to the chemical formula of a composite oxide of Fe, Mn, Nb, Cs, A and B. The molar content ratio of Fe, Mn, Nb, Cs, A and B in the active components can be obtained through the chemical formula. The molar content of Fe, Mn, Nb, Cs, A and B in the active components is the molar content of the corresponding elements provided by the corresponding raw materials when preparing the catalyst.
[0033] The new iron-based catalyst provided in the present invention has excellent resistance to carbon deposition when used, and can achieve high CO feedstock conversion rate and C2-C4 olefin selectivity when used in FTO reaction.
[0034] According to the present invention, as long as the purpose of the present invention can be achieved, the specific types of the non-ferrous metal elements of Group VIII and the elements of Group VIB are not particularly limited. In some preferred embodiments, A is selected from at least one of Co, Ni, Cu and Zn. The catalyst under this embodiment has better catalytic activity and resistance to carbon deposition.
[0035] According to the present invention, as long as the purpose of the present invention can be achieved, the specific selection of La series elements is not particularly limited. In some preferred embodiments, B is selected from at least one of La, Ce, Pr and Nd, preferably La. The catalyst under this embodiment has better catalytic activity and resistance to carbon deposition.
[0036] According to the present invention, in some preferred embodiments, a is in the range of 40.0-120.0, for example, 40.0, 50.0, 60.0, 70.0, 80.0, 90.0, 100.0, 120.0, or a range consisting of any two of the above values. In the catalyst of this embodiment, the components between the active components and the carrier can better cooperate to improve the anti-coking property and catalytic activity of the catalyst.
[0037] According to the present invention, in some preferred embodiments, b is in the range of 5.0-15.0, such as 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, or a range consisting of any two of the above values. In the catalyst of this embodiment, the components between the active components and the carrier can better cooperate to improve the anti-coking property and catalytic activity of the catalyst.
[0038] According to the present invention, in some preferred embodiments, c is in the range of 0.5-8.0, for example, 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, or a range consisting of any two of the above values. In the catalyst of this embodiment, the components between the active components and the carrier can better cooperate to improve the catalyst's resistance to carbon deposition and catalytic activity.
[0039] According to the present invention, in some preferred embodiments, the value range of d is 5.0-50.0, for example, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 12.0, 15.0, 20.0, 30.0, 40.0, 50.0, or a range consisting of any two of the above values. In the catalyst under this embodiment, the components between the active components and the carrier can better cooperate to improve the catalyst's resistance to carbon deposition and catalytic activity.
[0040] According to the present invention, in some preferred embodiments, the value range of e is 0.5-8.0, for example, 0.5, 1.0, 1.5, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, or a range consisting of any two of the above values. In the catalyst under this embodiment, the components between the active components and the carrier can better cooperate to improve the catalyst's resistance to carbon deposition and catalytic activity.
[0041] According to the present invention, as long as the purpose of the present invention can be achieved, the specific type of the carrier is not particularly limited. In some preferred embodiments, the carrier is selected from at least one of silicon dioxide, aluminum oxide and titanium oxide.
[0042] According to the present invention, in some preferred embodiments, based on the total weight of the catalyst, the content of the carrier is 5-60 weight%, for example, 5 weight%, 10 weight%, 20 weight%, 30 weight%, 40 weight%, 50 weight%, or a range consisting of any two of the above values, preferably 40-60 weight%.
[0043] According to the present invention, in some preferred embodiments, based on the total weight of the catalyst, the content of the active component is 40-95 weight%, for example, 5 weight%, 10 weight%, 20 weight%, 30 weight%, 40 weight%, 50 weight%, 75 weight%, 85 weight%, 95 weight%, or a range consisting of any two of the above values, preferably 40-60 weight%.
[0044] The second aspect of the present invention provides a method for preparing the iron-based catalyst of the present invention, the preparation method comprising:
[0045] (1) In the presence of a precipitant, a solution containing an Fe source, a Mn source, a Nb source and an A source undergoes a precipitation reaction;
[0046] (2) The precipitate obtained by the precipitation reaction in step (1) is mixed with the carrier source, Cs source solution, pH adjuster, and B source solution in sequence, and then dried and calcined.
[0047] The iron-based catalyst prepared in the present invention has excellent resistance to carbon deposition when used, and can achieve high CO feedstock conversion rate and C2-C4 olefin selectivity when used in FTO reaction.
[0048] According to the present invention, the solution containing Fe source, Mn source, Nb source and A source refers to a solution formed by a good solvent and Fe source, Mn source, Nb source and A source, wherein the Fe source, Mn source, Nb source and A source can be mixed with a good solvent respectively to obtain 4 groups of materials, and then the 4 groups of materials are mixed to obtain a solution containing Fe source, Mn source, Nb source and A source; the Fe source, Mn source, Nb source and A source can also be added to a good solvent at the same time to mix to obtain a solution containing Fe source, Mn source, Nb source and A source; the Fe source can also be mixed with a good solvent to obtain material I, the Nb source can be mixed with a good solvent to obtain material II, the Mn source and A source can be mixed with a good solvent to obtain material III, and then material I, material II and material III are mixed to obtain a solution containing Fe source, Mn source, Nb source and A source, but the formation of the solution containing Fe source, Mn source, Nb source and A source in the present invention is not limited to the above method; wherein, as long as the purpose of the present invention can be achieved, the selection of the above good solvent is not particularly limited, and the good solvents in the present invention are all selected from water.
[0049] According to the present invention, the contents of Fe source, Mn source, Nb source and A source in the solution containing Fe source, Mn source, Nb source and A source can be selected according to the corresponding contents of Fe, Mn, Nb and A of active components in the iron-based catalyst; the amount of water used is sufficient as long as it can dissolve the Fe source, Mn source, Nb source and A source and ensure the smooth progress of the precipitation reaction.
[0050] According to the present invention, there is no particular limitation on the selection of Fe source, Mn source, Nb source and A source, which may be salts corresponding to Fe, Mn, Nb and A, such as nitrate and / or oxalate.
[0051] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the precipitant is not particularly limited. In some embodiments, in step (1), the precipitant is an alkaline precipitant, preferably at least one of urea, ammonia water and ammonium bicarbonate.
[0052] According to the present invention, in some embodiments, in step (1), the amount of the precipitant is 30-50% of the total weight of the Fe source, Mn source, Nb source and A source.
[0053] According to the present invention, in some embodiments, in step (1), the conditions of the precipitation reaction include: the precipitation temperature is 70-95°C.
[0054] According to the present invention, in some embodiments, in step (1), the conditions of the precipitation reaction include: the precipitation time is 10-60 minutes.
[0055] According to the present invention, the precipitate obtained by the precipitation reaction in step (1) can be washed with water and separated to obtain the precipitate, and the present invention has no particular limitation on this.
[0056] According to the present invention, as long as the purpose of the present invention can be achieved, the type of carrier source is not particularly limited. In some embodiments, the carrier source is selected from a sol corresponding to the carrier, such as silica sol, aluminum sol or titanium sol. The catalyst obtained by adopting this embodiment has better carbon deposition resistance and catalytic activity.
[0057] According to the present invention, the Cs source solution refers to a solution formed by mixing a Cs source with a corresponding good solvent, and the amount of the good solvent is not particularly limited, as long as the Cs source can be fully dissolved; the good solvent in the present invention is all water, wherein the selection of the Cs source is not particularly limited, and it can be a Cs salt or a Cs hydroxide.
[0058] According to the present invention, the B source solution refers to a solution formed by mixing the B source with a corresponding good solvent, and the amount of the good solvent is not particularly limited, as long as the B source can be fully dissolved; wherein, the selection of the B source is not particularly limited, and the good solvent in the present invention is water, and can be a B salt, such as a nitrate.
[0059] According to the present invention, the contents of the Cs source and the B source can be selected according to the corresponding contents of Cs and B in the active components in the iron-based catalyst.
[0060] According to the present invention, in some preferred embodiments, in step (2), the amount of the pH regulator added is such that the pH value of the system is 5 to 6. The catalyst obtained by adopting this embodiment has better carbon deposition resistance and catalytic activity.
[0061] According to the present invention, as long as the purpose of the present invention can be achieved, the drying and roasting conditions in step (2) are not particularly limited. Preferably, the drying is spray drying, wherein spray drying can also form a solid substance of microspheres; preferably, the roasting temperature is 300-550°C; preferably, the roasting time is 0.5-5 hours.
[0062] According to the present invention, in some preferred embodiments, the preparation method of the iron-based catalyst of the present invention further comprises performing reduction treatment and carbonization treatment on the solid material obtained by calcination. By adopting the above-mentioned embodiment, the prepared catalyst not only has good catalytic activity, but also has excellent resistance to carbon deposition, and is used in the FTO reaction to produce C2-C4 olefins with high selectivity.
[0063] According to the present invention, in some preferred embodiments, the reducing atmosphere of the reduction treatment includes H2 and an inert gas, and the volume concentration of H2 in the reducing atmosphere is preferably 1-20%, for example, 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, or a range consisting of any two of the above values. Using the above embodiment, the prepared catalyst not only has good catalytic activity, but also has excellent resistance to carbon deposition, and is used in the FTO reaction to produce C2-C4 olefins with high selectivity.
[0064] According to the present invention, in some preferred embodiments, the conditions for the reduction treatment include: a pressure of 0-2 MPa.
[0065] According to the present invention, in some preferred embodiments, the reduction treatment conditions include: the solid material load is 3000-6000 mL·h -1 ·g -1 ; The solid matter here refers to the solid matter obtained after roasting.
[0066] According to the present invention, in some preferred embodiments, the conditions for the reduction treatment include: a heating rate of 1-15° C. / min.
[0067] According to the present invention, in some preferred embodiments, the reduction treatment conditions include: the reduction temperature is 200-450°C.
[0068] According to the present invention, in some preferred embodiments, the conditions for the reduction treatment include: the reduction time is 12-48 hours.
[0069] According to the present invention, in some particularly preferred embodiments, the carbonization atmosphere of the carbonization treatment comprises low carbon alkanes and inert gases.
[0070] According to the present invention, in some particularly preferred embodiments, the volume concentration of low-carbon alkanes in the carbiding atmosphere is 5-25%, for example, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 23%, 25%, or a range consisting of any two of the above values.
[0071] According to the present invention, in some particularly preferred embodiments, the preferred low carbon alkane is a C2-C4 alkane (e.g., ethane, propane, butane). Using the aforementioned embodiment, the prepared catalyst not only has good catalytic activity, but also has excellent resistance to carbon deposition, and is used in the FTO reaction to produce C2-C4 olefins with high selectivity.
[0072] According to the present invention, in some particularly preferred embodiments, the conditions for the carbonization treatment include: a pressure of 0-2 MPa.
[0073] According to the present invention, in some particularly preferred embodiments, the carbonization treatment conditions include: the solid material load is 3000-6000 mL·h -1 ·g -1 ; The solid substance here refers to the solid substance obtained after reduction treatment.
[0074] According to the present invention, in some particularly preferred embodiments, the conditions for the carbonization treatment include: a heating rate of 3-20° C. / min.
[0075] According to the present invention, in some particularly preferred embodiments, the conditions for the carbonization treatment include: the carbonization temperature is 200-450°C.
[0076] According to the present invention, in some particularly preferred embodiments, the conditions for the carbonization treatment include: the carbonization time is 12-48 hours.
[0077] The third aspect of the present invention provides the use of the iron-based catalyst of the present invention in a FTO reaction.
[0078] When the iron-based catalyst of the present invention is used in the FTO reaction, the raw material CO has a high conversion rate, and the C2-C4 olefins have a high selectivity, and the catalyst has a lower carbon deposition amount during long-term use.
[0079] A fourth aspect of the present invention provides a FTO reaction, in which H2 and CO are contact-reacted in the presence of the iron-based catalyst of the present invention.
[0080] According to the present invention, preferably, the H2 / CO molar ratio is 0.1-5.
[0081] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the contact reaction are not particularly limited. Preferably, the temperature during the contact reaction is 200-400°C; preferably, the reaction pressure during the contact reaction is 0.5-10MPa; preferably, the volume space velocity of the mixture of H2 and CO is 100-8000mL·h -1 ·g -1 .
[0082] The present invention will be described in detail below through examples.
[0083] The iron-based catalysts prepared in the examples and comparative examples were used to carry out the direct preparation of light olefins from synthesis gas under the following conditions:
[0084] The reactor and process conditions are as follows:
[0085] Millimeter Fluidized Bed Reactor
[0086] Reaction temperature 360℃
[0087] Reaction pressure 1.2MPa
[0088] The catalyst loading is equivalent to 80g of catalyst before reduction
[0089] Based on the amount of catalyst before reduction, the catalyst loading was 4500 mL·h -1 ·g -1
[0090] Raw material ratio (molar) H2 / CO=1.8 / 1.
[0091] Example 1
[0092] Take 568.9 grams of ferric nitrate nonahydrate, add 1000 grams of water to dissolve, and obtain material I. Take 37.9 grams of niobium oxalate, add 100 grams of water and heat to dissolve, and obtain material II. Take 201.6 grams of 50wt% manganese nitrate and 17.0 grams of copper nitrate trihydrate in the same container, add 100 grams of water, and stir to dissolve to obtain material III.
[0093] Mix materials I, II and III, add 250 g of urea, heat to 90°C under stirring for precipitation reaction, and keep at 90°C for 30 minutes; then wash with water and separate to obtain a precipitate;
[0094] 423.8 g of 40% (weight) silica sol material was added to the above precipitate under stirring, and then 50 g of a solution containing 1.05 g of CsOH was added, and the pH value of the above slurry was adjusted with ammonia water so that the pH of the mixed slurry was 6.0. After stirring evenly, 50 g of an aqueous solution containing 3.0 g of lanthanum nitrate hexahydrate was added, and the mixture was stirred thoroughly to obtain a slurry;
[0095] The well-stirred slurry was formed into microspheres in a spray dryer and finally calcined at 500°C for 2.0 hours in a rotary calciner with an inner diameter of 89 mm and a length of 1700 mm (φ89×1700 mm). The resulting solid was then subjected to reduction treatment: a H2 / N2 mixed gas with a volume concentration of 10% (H2) was used and the temperature was raised to 380°C at 5°C / min; a pressure of 0.6 MPa, a solid loading of 80 g, and a catalyst loading of 5500 mL·h was used. -1 ·g -1 , 380 ℃ for 24 hours; finally, the obtained solid was carbonized: using a C2H6 / N2 mixed gas with a volume concentration of 15% (C2H6), the temperature was raised to 380 ℃ at 10 ℃ / min, and the pressure was 0.6MPa, the solid loading was 80g, and the solid load was 5500mL·h -1 ·g -1 , maintained at 380°C for 24 hours for carbonization treatment, and finally an iron-based catalyst was obtained.
[0096] The iron-based catalyst composition is as follows (active components are expressed in the form of oxides): 50 wt% Fe 100 Mn 40.0 Nb 5.0 Cs 0.5 Cu 5.0 La 0.5 O x +50 wt.% SiO2.
[0097] The prepared iron-based catalyst was used to directly prepare light olefins from synthesis gas. The reaction was run for 300 hours. The results are shown in Table 1.
[0098] Example 2
[0099] Take 568.9 grams of ferric nitrate nonahydrate, add 1000 grams of water to dissolve, and obtain material I. Take 76 grams of niobium oxalate, add 200 grams of water and heat to dissolve, and obtain material II. Take 252 grams of 50wt% manganese nitrate and 20.5 grams of copper nitrate trihydrate in the same container, add 100 grams of water, and stir to dissolve to obtain material III.
[0100] Mix materials I, II and III, add 300 g of urea, heat to 80°C under stirring for precipitation reaction, and keep at 90°C for 40 minutes; then wash with water and separate to obtain a precipitate;
[0101] 490 g of 40% (weight) silica sol material was added to the above precipitate under stirring, and then 50 g of a solution containing 8.5 g of CsOH was added, and the pH value of the above slurry was adjusted with ammonia water so that the pH of the mixed slurry was 6.0. After stirring evenly, 150 g of an aqueous solution containing 12.2 g of lanthanum nitrate hexahydrate was added, and the mixture was stirred thoroughly to obtain a slurry;
[0102] The well-stirred slurry was formed into microspheres in a spray dryer and finally calcined at 500°C for 2.0 hours in a rotary calciner with an inner diameter of 89 mm and a length of 1700 mm (φ89×1700 mm). The resulting solid was then subjected to reduction treatment: a H2 / N2 mixed gas with a volume concentration of 15% (H2) was used and the temperature was raised to 400°C at 10°C / min; a pressure of 1 MPa, a solid loading of 80 g, and a solid load of 5000 mL·h was used. -1 ·g -1 , 400 ℃ for 24 hours; finally, the obtained solid was carbonized: using a C2H6 / N2 mixed gas with a volume concentration of 20% (C2H6), the temperature was raised to 400 ℃ at 15 ℃ / min, and the pressure was 1MPa, the solid loading was 80g, and the solid load was 5000mL·h -1 ·g -1 , maintained at 400℃ for 24 hours, and finally an iron-based catalyst was obtained.
[0103] The iron-based catalyst composition is as follows (active components are expressed in the form of oxides): 50 wt% Fe 100 Mn 50.0 Nb 10.0 Cs 4.0 Cu 6.0 La 2.0 O x +50 wt.% SiO2.
[0104] The prepared iron-based catalyst was used to directly prepare light olefins from synthesis gas. The reaction was run for 300 hours. The results are shown in Table 1.
[0105] Example 3
[0106] Take 568.9 grams of ferric nitrate nonahydrate, add 1000 grams of water to dissolve, and obtain material I. Take 45.5 grams of niobium oxalate, add 120 grams of water and heat to dissolve, and obtain material II. Take 201.6 grams of 50wt% manganese nitrate and 41 grams of cobalt nitrate hexahydrate in the same container, add 120 grams of water, and stir to dissolve to obtain material III.
[0107] Mix materials I, II and III, add 250 g of urea, heat to 90°C under stirring for precipitation reaction, and keep at 90°C for 30 minutes; then wash with water and separate to obtain a precipitate;
[0108] 434 g of 40% (by weight) titanium sol material was added to the above precipitate under stirring, and then 50 g of a solution containing 1.05 g of CsOH was added, and the pH value of the above slurry was adjusted with ammonia water so that the pH of the mixed slurry was 6.0. After stirring evenly, 50 g of an aqueous solution containing 3.0 g of lanthanum nitrate hexahydrate was added, and the mixture was stirred thoroughly to obtain a slurry;
[0109] The well-stirred slurry was formed into microspheres in a spray dryer and finally calcined at 550°C for 2.0 hours in a rotary calciner with an inner diameter of 89 mm and a length of 1700 mm (φ89×1700 mm). The solid was then reduced by heating to 380°C at 5°C / min with a H2 / N2 mixture of 10% (H2) by volume; the solid was charged at a pressure of 0.6 MPa, a solid loading of 80 g, and a catalyst loading of 4500 mL·h. -1 ·g -1 , 380 ℃ for 24 hours; finally, the obtained solid was carbonized: using a C2H6 / N2 mixed gas with a volume concentration of 18% (C3H8), the temperature was raised to 380 ℃ at 10 ℃ / min, and the pressure was 0.6MPa, the solid loading was 80g, and the solid load was 4500mL·h -1 ·g -1 , maintained at 380 °C for 24 hours, and finally an iron-based catalyst was obtained.
[0110] The iron-based catalyst composition is as follows (active components are expressed in the form of oxides): 50 wt% Fe 100 Mn 40.0 Nb 6.0 Cs 0.5 Co 10.0 La 0.5 O x +50 wt.% TiO2.
[0111] The prepared iron-based catalyst was used to directly prepare light olefins from synthesis gas. The reaction was run for 300 hours. The results are shown in Table 1.
[0112] Example 4
[0113] The method of Example 1 is different from that of Example 1:
[0114] Take 568.9 grams of ferric nitrate nonahydrate, add 1000 grams of water to dissolve, and obtain material I. Take 37.9 grams of niobium oxalate, add 100 grams of water, heat and dissolve, and obtain material II. Take 201.6 grams of 50 wt% manganese nitrate and 1.05 grams of CsOH, add 100 grams of water, stir and dissolve, and obtain material III.
[0115] Mix materials I, II and III, add 250 g of urea, heat to 90°C under stirring for precipitation reaction, and keep at 90°C for 30 minutes; then wash with water and separate to obtain a precipitate;
[0116] 423.8 g of 40% (weight) silica sol material was added to the above precipitate under stirring, and then 100 g of a solution containing 17.0 g of copper nitrate trihydrate was added, and the pH value of the above slurry was adjusted with ammonia water so that the pH of the mixed slurry was 6.0. After stirring evenly, 50 g of an aqueous solution containing 3.0 g of lanthanum nitrate hexahydrate was added, and the mixture was stirred thoroughly to obtain a slurry;
[0117] The remaining steps are the same as those in Example 1, and an iron-based catalyst is finally obtained.
[0118] The iron-based catalyst composition is as follows (active components are expressed in the form of oxides): 50 wt% Fe 100 Mn 40.0 Nb 5.0 Cs 0.5 Cu 5.0 La 0.5 O x +50 wt.% SiO2.
[0119] The prepared iron-based catalyst was used to directly prepare light olefins from synthesis gas. The reaction was run for 300 hours. The results are shown in Table 1.
[0120] Example 5
[0121] The method of Example 1 is different from that of Example 1:
[0122] Without carbonization treatment, the remaining steps are the same, that is, the iron-based catalyst is directly obtained after the reduction treatment.
[0123] The prepared iron-based catalyst was used to directly prepare light olefins from synthesis gas. The reaction was run for 300 hours. The results are shown in Table 1.
[0124] Example 6
[0125] The method of Example 1 is different from that of Example 1:
[0126] The C2H4 / N2 mixed gas with a volume concentration of 15% (C2H6) was replaced by a C2H4 / N2 mixed gas with a volume concentration of 15% (ethylene), and the remaining steps were the same, and finally an iron-based catalyst was obtained.
[0127] The prepared iron-based catalyst was used to directly prepare light olefins from synthesis gas. The reaction was run for 300 hours. The results are shown in Table 1.
[0128] Example 7
[0129] The method of Example 1 is different from that of Example 1:
[0130] The C2H6 / N2 mixed gas with a volume concentration of 15% (C2H6) is replaced by a C2H6 / N2 mixed gas with a volume concentration of 40% (C2H6), and the remaining steps are the same, and finally an iron-based catalyst is obtained.
[0131] The prepared iron-based catalyst was used to directly prepare light olefins from synthesis gas. The reaction was run for 300 hours. The results are shown in Table 1.
[0132] Example 8
[0133] The method of Example 1 is different from that of Example 1:
[0134] A H2 / N2 mixed gas with a volume concentration of 30% (H2) was used to replace a H2 / N2 mixed gas with a volume concentration of 10% (H2), and the remaining steps were the same, and finally a catalyst was obtained.
[0135] The prepared iron-based catalyst was used to directly prepare light olefins from synthesis gas. The reaction was run for 300 hours. The results are shown in Table 1.
[0136] Comparative Example 1
[0137] Take 568.9 grams of ferric nitrate nonahydrate, add 1000 grams of water to dissolve, and obtain material I. Take 201.6 grams of 50wt% manganese nitrate and 17.0 grams of copper nitrate trihydrate in the same container, add 100 grams of water, stir and dissolve to obtain material III.
[0138] Mix materials I and III, add 250 g of urea, heat to 90°C with stirring to carry out precipitation reaction, and keep at 90°C for 30 minutes; then wash with water and separate to obtain a precipitate.
[0139] 423.8 g of 40% (weight) silica sol material was added to the above precipitate under stirring, and then 50 g of a solution containing 1.1 g of CsOH was added, and the pH value of the above slurry was adjusted with ammonia water so that the pH of the mixed slurry was 6.0. After stirring evenly, 50 g of an aqueous solution containing 3.0 g of lanthanum nitrate hexahydrate was added, and the mixture was stirred thoroughly to obtain a slurry;
[0140] The fully stirred slurry was formed into microspheres in a spray dryer, and finally calcined at 500°C for 2.0 hours in a rotary calcining furnace with an inner diameter of 89 mm and a length of 1700 mm (φ89×1700 mm);
[0141] The obtained solid was subjected to reduction treatment: a H2 / N2 mixed gas with a volume concentration of 10% (H2) was heated to 380°C at 5°C / min; a pressure of 0.6 MPa, a solid loading of 80 g, and a solid load of 5500 mL·h -1 ·g -1 , 380 ℃ for 24 hours; finally, the obtained solid was carbonized: using a C2H6 / N2 mixed gas with a volume concentration of 15% (C2H6), the temperature was raised to 380 ℃ at 10 ℃ / min, and the pressure was 0.6MPa, the solid loading was 80g, and the solid load was 5500mL·h -1 ·g -1 , maintained at 380 °C for 24 hours, and finally an iron-based catalyst was obtained.
[0142] The iron-based catalyst composition is as follows (active components are expressed in the form of oxides): 50 wt% Fe 100 Mn 40.0 Cs 0.5 Cu 5.0 La 0.5 O x +50 wt% SiO2
[0143] The prepared iron-based catalyst was used to directly prepare light olefins from synthesis gas. The reaction was run for 300 hours. The results are shown in Table 1.
[0144] Table 1
[0145]
[0146]
[0147] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An iron-based catalyst, characterized in that The catalyst comprises a carrier and an active component. In terms of atomic ratio, the chemical formula of the active component expressed as an oxide is as follows: Fe 100 Mn a Nb b Cs c A d B e O x , A is selected from non-ferrous metal elements of Group VIII and / or elements of Group VIB; B is selected from La series elements; The value range of a is 30.0-130.0; The value range of b is 1.0-20.0; The value range of c is 0.1-10.0; The value range of d is 1.0-60.0; The value range of e is 0.1-10.0; x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst.
2. The catalyst according to claim 1, wherein A is at least one selected from Co, Ni, Cu and Zn; and / or B is at least one selected from La, Ce, Pr and Nd.
3. The catalyst according to claim 1 or 2, wherein a has a value in the range of 40.0-120.0; and / or b ranges from 5.0 to 15.0; and / or The value of c ranges from 0.5 to 8.0; and / or The value of d is in the range of 5.0-50.0; and / or The value range of e is 0.5-8.
0.
4. The catalyst according to any one of claims 1 to 3, wherein The carrier is selected from at least one of silicon dioxide, aluminum oxide and titanium oxide; and / or Based on the total weight of the catalyst, the content of the carrier is 5-60% by weight.
5. A method for preparing the catalyst according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) In the presence of a precipitant, a solution containing an Fe source, a Mn source, a Nb source and an A source undergoes a precipitation reaction; (2) The precipitate obtained from the precipitation reaction in step (1) is sequentially mixed with a carrier source, a Cs source solution, a pH adjuster, and a B source solution, and then dried and calcined.
6. The preparation method according to claim 5, wherein: The preparation method further comprises: performing reduction treatment and carbonization treatment on the solid material obtained by roasting; Preferably, the reducing atmosphere of the reduction treatment comprises H2 and an inert gas, and preferably the volume concentration of H2 in the reducing atmosphere is 1-20%; and / or The conditions for the reduction treatment include: a pressure of 0-2 MPa; and / or, the solid material loading is 3000-6000 mL·h -1 ·g -1 ; and / or, the heating rate is 1-15°C / minute; and / or, the reduction temperature is 200-450°C; and / or, the reduction time is 12-48 hours.
7. The method according to claim 6, wherein: The carbonization atmosphere of the carbonization treatment comprises low carbon alkanes and inert gas, preferably the low carbon alkanes are C2-C4 alkanes; and / or the volume concentration of the low carbon alkanes in the carbonization atmosphere is 5-25%; and / or The carbonization treatment conditions include: a pressure of 0-2 MPa; and / or a solid material load of 3000-6000 mL·h -1 ·g -1 ; and / or, the heating rate is 3-20°C / minute; and / or, the carbonization temperature is 200-450°C; and / or, the carbonization time is 12-48 hours.
8. The preparation method according to any one of claims 5 to 7, wherein: In step (1), the precipitant is an alkaline precipitant, preferably at least one of urea, ammonia water and ammonium bicarbonate; and / or In step (1), the amount of the precipitant is 30-50% of the total weight of the Fe source, Mn source, Nb source and A source; and / or In step (1), the conditions of the precipitation reaction include: a precipitation temperature of 70-95° C.; and / or a precipitation time of 10-60 minutes; and / or In step (2), the carrier source is selected from a sol corresponding to the carrier; and / or In step (2), the amount of the pH adjuster added is such that the pH value of the system is 5-7.
9. Use of the iron-based catalyst according to any one of claims 1 to 4 in a FTO reaction.
10. A FTO reaction, characterized in that The reaction comprises: in the presence of the iron-based catalyst described in any one of claims 1 to 4, H2 and CO are contacted and reacted.
Citation Information
Patent Citations
Catalyst for preparing light olefin from synthesis gas and preparation method thereof
CN105854915A
Multi-metal oxide catalyst and preparation method thereof
CN102989471A
Iron-based catalyst for direct synthesis of low-carbon olefin from synthesis gas
CN107913718A
Iron-based catalyst for preparation of low carbon olefin by synthesis gas one-step method
CN109647428A
Fischer-tropsch synthesis fe-based catalyst, process of preparation and application thereof
US20110294908A1